Analisis Penilaian Kinerja Keuangan Menggunakam Penerapan Economic Value Added Pada PT. Fiber Networks Indonesia - Siti Nurhalizah; Dhuha Safria; Chanissa Purwaningrum (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Financial performance assessment is essential in creating added value for shareholders, especially when a company faces operational and capital management challenges. This study aims to analyze the financial performance of PT Fiber Networks Indonesia using the Economic Value Added (EVA) method to evaluate the extent to which the company is able to generate economic value. The research employs a quantitative non-statistical approach, utilizing secondary data obtained from the company’s annual financial statements. The EVA calculation in this study considers three main variables: NOPAT, WACC, and Invested Capital. The results indicate that the company did not create economic value in all observed years. For instance, in 2022, the EVA value was negative, implying that the company had not yet covered its cost of capital. However, in 2024, the EVA turned positive, reflecting improved efficiency and the success of implemented financial strategies. The study concludes that EVA trends fluctuated, showing a downward tendency from 2021 to 2023, before increasing again in 2024. Factors influencing EVA include operational efficiency, capital structure, and investment management. It is recommended that PT Fiber Networks Indonesia continue enhancing operational efficiency, optimizing capital structure, and strengthening communication with shareholders to ensure sustainable economic value creation.